Psychophysiological coherence training to moderate air traffic controllers’ fatigue on rotating roster - Li, Wen-Chin; Zhang, Jingyi; Kearney, Peter (Wiley, 2022)
The nature of the current rotating roster, providing 24-h air traffic services over five irregular shifts, leads to accumulated fatigue which impairs air traffic controllers’ cognitive function and task performance. It is imperative to develop an effective fatigue risk management system to improve aviation safety based upon scientific approaches. Two empirical studies were conducted to address this issue. Study 1 investigated the mixed effect of circadian rhythm disorders and resource depletion on controllers’ accumulated fatigue. Then, study 2 proposed a potential biofeedback solution of quick coherence technique which can mitigate air traffic controllers’ (ATCOs’) fatigue while on controller working position and improve ATCOs’ mental/physical health. The current two-studies demonstrated a scientific approach to fatigue analysis and fatigue risk mitigation in the air traffic services domain. This research offers insights into the fluctuation of ATCO fatigue levels and the influence of a numbers of factors related to circadian rhythm and resource depletion impact on fatigue levels on study 1; and provides psychophysiological coherence training to increase ATCOs’ fatigue resilience to mitigate negative impacts of fatigue on study 2. Based on these two studies, the authors recommended that an extra short break for air traffic controllers to permit practicing the quick coherence breathing technique for 5 min at the sixth working hour could substantially recharge cognitive resources and increase fatigue resilience. Application: Present studies highlight an effective fatigue intervention based on objective biofeedback to moderate controllers’ accumulated fatigue as a result of rotating shift work. Accordingly, air navigation services providers and regulators can develop fatigue risk management systems based on scientific approaches to improve aviation safety and air traffic controller's wellbeing.
Keywords: air traffic services; fatigue risk management; heart rate variability; psychophysiological coherence; rotating shifts